1957
DOI: 10.1021/ac60122a023
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum Fusion Determination of Oxygen and Nitrogen Lanthanum

Abstract: The opinions or assertions contained in this article are the private ones of the writers and are not to be construed as official or reflecting the views of the Navy Department.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1962
1962
1986
1986

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…This technique offers, therefore, a means of estimating the reliability of oxygen values by its wider choice of analyzing conditions using various bath metals with a wider choice of analyzing temperatures between 800--2200 ~ No literature, however, is known on the determination of oxygen in gadolinium and terbium, with a high volatility and a high reactivity with oxygen, and there is no discussion on the accuracy of the determination of these metals. Peterson et al [2] only reported that oxygen in lanthanum was determined with a nickel bath using vacuum fusion analysis, and the recovery of oxygen was 90 percent presumably due to the gettering effect of the sample vapor in the furnace.…”
mentioning
confidence: 99%
“…This technique offers, therefore, a means of estimating the reliability of oxygen values by its wider choice of analyzing conditions using various bath metals with a wider choice of analyzing temperatures between 800--2200 ~ No literature, however, is known on the determination of oxygen in gadolinium and terbium, with a high volatility and a high reactivity with oxygen, and there is no discussion on the accuracy of the determination of these metals. Peterson et al [2] only reported that oxygen in lanthanum was determined with a nickel bath using vacuum fusion analysis, and the recovery of oxygen was 90 percent presumably due to the gettering effect of the sample vapor in the furnace.…”
mentioning
confidence: 99%